ANALISIS PENGELOMPOKAN MAHASISWA KKN BERDASARKAN KRITERIA JENIS KELAMIN, FAKULTAS DAN SEKOLAH - Vandu Riski Muwisnawangsa; Aristoteles Aristoteles (Universitas Lampung, 2017)
Activity of Community Service Program/Kuliah Kerja Nyata (KKN) at Lampung University is an intra-curricular activity that combines the implementation of Tri Dharma Perguruan Tinggi with a method of providing learn and work experience to students in community development activities. Grouping students KKN performed with greedy algorithm. To find out the accuracy of grouping students of KKN, the necessary analysis is based on the criteria of gender, faculty and school. Analysis of the grouping will be used as a reference in view of accuracy randomization KKN group that has been done. Analysis grouping students of KKN carried out in three categories: regular, FKIP and combined regular WITH FKIP. Keywords: Analysis, Greedy Algorithm, KKN ( Kuliah Kerja Nyata ) / Community Service Program